(untitled) (Journal of history, 2019)
In Kazakhstan, the first Stone Age was discovered by geologists in 1950 in the Karatau Range. After the opening of the first of these Stone Age geologists, Institute of History, Archaeology and Ethnology of the Kazakh SSR them. C.C. Ualihanov creates a detachment of the Stone Age to study the Karatau Ridge 1957. Commanded a prominent specialist Stone Age H.A. Alpysbayev. Go to the above scientific research team were published the first work on the Stone Age. H.A. Alpysbayev is the founder of Kazakhstan Paleolithic school.